PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA GURU TK DI WILAYAH II KECAMATAN PESANGGRAHAN - Hendri Jopanda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2017)
In the overall educational process, teachers are the dominant determinant in education because teachers are professional educators with the primary task of educating, teaching, guiding, directing, training, assess and evaluate students. A professional teacher is charged with a number of requirements, among others qualified professional education, scientific competence according they are engaged in, the ability to communicate well with their students, have a creative spirit and productive, has a work ethic and a commitment to the profession and always conduct self-development continuously. However, in practice there are still often found limitations both individually and institution. The purpose of this research is to know the effect of competence, work environment and compensation on the performance of kindergarten teachers in region II Pesanggrahan. The research used survey methods by distributing questionnaires. The research population is all teachers in region II Pesanggrahan amounted to 141 teachers which are 59 teachers as samples using cluster random sampling method. The analysis used is multiple linear regression analysis. The results of this research indicate the competence has a positive and significant effect on teacher performance and the work environment also compensation has no positive and significant effect on teacher performance. Simultaneously competence, work environment and compensation have a positive and significant influence on teacher performance.